DOZ047.22: FEED-EASY: feeding disorders in children with esophageal atresia study. (24th June 2019) - Pham, A; Dugelay, E; Bonnard, A; Gelas, T; Rousseau, V; Thomassin, N; Cabon-Boudard, I; Michaud, L; Guinot, A; Rebeuh, J; Mandat, A L E; Djeddi, D; et al.
Abstract: Introduction: With advances in surgical and neonatal care, survival of patients with esophageal atresia (EA) has improved over time. While a number of conditions associated with EA may have an impact on feeding development (delayed primary anastomosis, anastomotic leaks, recurrent tracheoesophageal fistula, anastomotic stricture, gastroesophageal reflux, esophageal dysmotility, etc.) and although children with EA experience a number of oral aversive events in their first year of life, feeding disorders (FD) are poorly described and frequently unrecognized. The primary aim of this study was to describe FD in children born with EA, with a standardized scale. The secondary aim was to describe conditions associated with FD. Methods: FEED-EASY is a multicentric French study. Parents of children born with EA between 2013 and 2016 in one of the 22 participating centers were asked to participate and received the French version of the standardized and reproductive 'Montreal Children's Hospital Feeding Scale (MCH-FS)'. Results: One hundred and forty-five children were included; 61 (42%) had FD according to the MCH-FS. These children were characterized by disinterest in food, oral hypersensitivity, difficulty in touching some textures and food avoidance, with an influence in quality of life. Nineteen (13%) were tube-fed between 1 and 4 years of age. Birth weight and chronic respiratory difficulties were associated with FD in children with EA. Anastomotic stricture (present in 31% of the included children) was not associated with FD. Conclusions: FD is frequent and unrecognized in children with EA, and can influence growth and quality of life. MCH-FS allows pediatricians to identify FD in children with EA within a couple of minutes.